Landslide in Chittagong City: A Perspective on Hill Cutting - Chisty, Kutub Uddin (Journal of Bangladesh Institute of Planners, 2014)
Hills are our resources. Plundering of hills is a crime; a crime against our environment and sustainability. Chittagong has already lost a number of hills to the land grabbers due to massive hill cutting. A number of undulating hills located in Chittagong but hills which have already been cutting for housing purposes can no longer to residential area development. Unplanned hill cutting in the Chittagong city has become a major humanitarian issue when it occur landslides. Every year landslide is causing death of valuable lives and property loss. Strategies are adapted for hill preservation in Chittagong city master plan and detail area plan (DAP) but lack of interorganizational coordination sustainable land management is not carrying out activities related to hill cutting. City is expanded as hill cutting in city area is also increased. The present paper focuses on the land cover changing profile and hill cutting scenarios of Chittagong city corporation area and how hill cutting sequenced landslide. The landslide tragedies in Chittagong city are the examples of law enforcement failure. Once lost, it won’t be able to get them back so planning intervention is necessary. Journal of Bangladesh Institute of Planners, Vol. 7, Dec 2014, pp. 79-95